The validity and reliability of an integrated approach for quantifying match physical-tactical performance - Ju, Wonwoo; J Lewis, Collin; Evans, Mark; Laws, Andy; S Bradley, Paul (Biology of Sport, 2022)
This study aimed to: (1) develop an integrated approach to quantifying match physical-tactical performance and (2) comprehensively examine the validity and reliability of this novel approach. Both UEFA qualified coaches and performance analysts (n = 30) participated to verify the scientific robustness of this new method. The percentage of correct responses were used to verify the validity of the integrated approach and the minimum acceptable agreement was set at 80%. Two well-trained groups of observers analysed a randomly selected English Premier League match for inter- and intra-observer reliability using the kappa statistic. A high degree of validity was demonstrated as the mean percentage of correct responses by all participants, accounting for 91.8 ± 4.3% for all, 92.2 ± 4.7% for out-of-possession, and 91.6 ± 5.7% for in-possession physical-tactical variables. Inter- and intra-observer reliability were found to be strong (κ = 0.81) to almost perfect (κ = 0.94), respectively. Additional analyses demonstrated that there was a nearly perfect correlation between data derived from the novel filter used for the present study to capture high-intensity running and those obtained from the filter of the commercial data provider (r = 0.99; P < 0.01). The data demonstrates that the integrated approach is valid and reliable regarding the quantification of physical-tactical performances. Therefore, it is now possible to unveil unique high-intensity profiles of elite players related to key tactical actions. This may help coaches and practitioners better understand the physical-tactical performances of players, as well as effectively translate physical metrics into training.